2011
DOI: 10.1007/s00774-011-0294-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of lean body mass and physical activity in bone health in children

Abstract: In the context of physical education curricula, markers of physical fitness (e.g., aerobic capacity, muscular strength, flexibility, and body mass index or body fat) are usually evaluated in reference to health standards. Despite their possible mediating role in the relationship between weight-bearing or muscle forces and features of bone tissue, these attributes of fitness may not be the most relevant to predict skeletal health. It is therefore important to analyze the relative contribution of these factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 47 publications
6
47
2
1
Order By: Relevance
“…Given the established crosstalk between exercise, metabolism and the musculoskeletal system[22,23], we examined the effects of IL15/IL15RA signaling on bone mineralization and osteoblast function in a mouse model lacking Il15ra (Il15ra −/− ). Using ex vivo bone imaging, mechanical testing and histological analysis, we evaluated bone mineralization and morphogenesis in Il15ra −/− femurs.…”
Section: Introductionmentioning
confidence: 99%
“…Given the established crosstalk between exercise, metabolism and the musculoskeletal system[22,23], we examined the effects of IL15/IL15RA signaling on bone mineralization and osteoblast function in a mouse model lacking Il15ra (Il15ra −/− ). Using ex vivo bone imaging, mechanical testing and histological analysis, we evaluated bone mineralization and morphogenesis in Il15ra −/− femurs.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five to forty minutes of vigorous PA per day has been suggested as a minimum daily dose for optimal bone growth [23][26] but the relationship between bone mineral accrual and PA during the growing years has not been thoroughly examined. Of the studies that exist, there is a lack of consensus on whether sex moderates the association between mechanical loading and bone accrual at the proximal femur [18], [19], [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that the proximal femur of boys’ is more sensitive to mechanical loading than girls’ [27]. This idea was not derived from work specifically powered to examine sex differences [23], [27][31]. Furthermore, most studies reporting a lower responsiveness of PA in girls (when compared to boys) analysed only the femoral neck and not other sub-regions of the proximal femur (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Body lean mass and bone size are closely related (Ferretti et al 2003; Ferretti et al 2001; Cointry et al 2004). It has been demonstrated that lean mass can predict bone size in pre-pubertal children and can serve as a major determinant of bone size (Martin 2002; Micklesfield et al 2011; Baptista et al 2012). Bone size, in turn, has been shown to be adapted to the dynamic load imposed by muscle force.…”
Section: Introductionmentioning
confidence: 99%